Intelligent Data Engineering and Automated Learning - IDEAL 2011 12th International Conference, Norwich, UK, September 7-9, 2011. Proceedings - Yin, Hujun; Wang, Wenjia; Rayward-Smith, Victor; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 12th International Conference on Intelligent Data Engineering and Automated Learning, IDEAL 2011, held in Norwich, UK, in September 2011. The 59 revised full papers presented were carefully reviewed and selected from numerous submissions for inclusion in the book and present the latest theoretical advances and real-world applications in computational intelligence.
Keywords: Computer science; Computer software; Database management; Information storage and retrieval systems; Information systems; Artificial intelligence; Computer Science; Artificial Intelligence (incl. Robotics).; Information Systems Applications (incl.Internet).; Database Management; Information Storage and Retrieval; Computation by Abstract Devices; Algorithm Analysis and Problem Complexity